Acute right ventricular failure - Bakšytė, Giedrė; Pieteris, Linas; Macas, Andrius (Acta medica Lituanica, 2012)
Acute right ventricular (RV) failure is a serious clinical challenge not only in cardiology intensive care but in adult critical care in general. It is related not only to left ventricular failure but also to a number of other causes of pulmonary vascular dysfunction and pulmonary hypertension (PH), for example, PH due to hypoxia, thromboembolism, mechanical ventilation or portopulmonary hypertension. Acute RV failure is often difficult to manage and it is associated with a worse prognosis. Mortality from cardiogenic shock due to RV infarction (>50%) exceeds that due to left ventricular disease. Acute RV failure is also related to increased mortality after surgical procedures. The general principles of management include pre-load optimization, increase in RV inotropy and after-load reduction by lowering pulmonary vascular resistance. This review focuses on the principles of RV failure management including general measures, vasoactive substances, ventilation strategies, surgical as well as mechanical approaches.
Keywords: right ventricle; right ventricular failure; acute heart failure; pulmonary hypertension; management; pulmonary vasodilators